Diagnostic predictive value of the Bladder EpiCheck test in the follow‐up of patients with non–muscle‐invasive bladder cancer. Issue 7 (2nd June 2019) - Trenti, Emanuela; D'Elia, Carolina; Mian, Christine; Schwienbacher, Christine; Hanspeter, Esther; Pycha, Alexander; Kafka, Mona; Degener, Stephan; Danuser, Hansjörg; Roth, Stephan; Pycha, Armin
Abstract : Background: The objective of this study was to evaluate the diagnostic accuracy of the Bladder EpiCheck test in the follow‐up of patients with non–muscle‐invasive bladder cancer (NMIBC) and to compare it with the accuracy of urinary cytology, cystoscopy, and/or histology. Methods: In total, 243 patients were enrolled in the current study. Patients were evaluated by voided urine cytology, by the Bladder EpiCheck test, and by white‐light cystoscopy. Results: Overall sensitivity was 33.3% for cytology, 62.3% for Bladder EpiCheck, and 66.7% for the 2 tests combined. The sensitivity of cytology increased from 7.7% in low‐grade (LG) tumors to 66.6% in high‐grade (HG) tumors; whereas, for the Bladder EpiCheck test, the sensitivity was 46.1% in LG tumors and 83.3% in HG tumors. Combined cytology and Bladder EpiCheck testing yielded an overall sensitivity of 56.4% for LG tumors and 90% for HG tumors. Overall specificity was 98.6% for cytology, 86.3% for Bladder EpiCheck, and 85.6% for the 2 tests combined. The positive predictive value was 92% for cytology and 68.2% for Bladder EpiCheck. For the 2 tests combined, it was 68.6%. The negative predictive value was similar for the 2 tests: 75.8% for cytology, 82.9% for Bladder EpiCheck, and 84.5% for the 2 tests combined. Conclusions: The sensitivity of the Bladder EpiCheck test was significantly higher than that of cytology. The test performed very well in terms of specificity but could not reach the high value of cytology. The positive predictive value was higher for Bladder EpiCheck, whereas the negative predictive value was approximately the same for both tests. Abstract : Bladder EpiCheck is a promising urinary marker but needs further optimization in terms of performance and costs. It may be used in combination with cytology to reduce invasiveness in the follow‐up of non–muscle‐invasive bladder cancer, decreasing discomfort for the patients and costs.